Karakteristik Sistem Pembayaran Transaksi Elektronik melalui Layanan Self-Service: Studi Terrace Abah Choi - Maulana, Muhammad Asrul; Kolopita, Kurnia Ningsih; Sonia, Citra; Rosnawati, Emy (Kertha Patrika, 2023)
This research will focus on analyzing the law of Electronic Payment System Operators through Supermarkets to find legal certainty for electronic agreements, and the practice of electronic agreements at Cafe Abah Choi, so that they can find solutions in the form of optimizing payment systems for electronic transactions through Supermarkets. This study employs an empirical (Sociolegal) method with a conflict approach. The results of this study are that the optimization of the electronic transaction system at the Abah Choi cafe can be implemented in the form of additions that must be equipped with a reliable security system, such as data encryption and strong user authentication. To further increase the sophistication of electronic self-service systems, new features can be developed in the future, such as payments using mobile payment technology or NFC (Near Field Communication). As well as the role of AI (Artificial Intelligence) technology can be used to manage electronic self-service systems automatically, such as monitoring inventory, analyzing customer data, or providing real-time customer service.